2003
DOI: 10.1002/crat.200310075
|View full text |Cite
|
Sign up to set email alerts
|

Beam induced lateral epitaxy: a new approach for lateral growth in molecular beam epitaxy

Abstract: Epitaxial lateral growth has been conducted without using oxide masks by a new technique called as beam induced lateral epitaxy (BILE). In this technique, molecular beams are sent in a glancing angle with respect to a substrate in MBE and a large lateral growth was accomplished on a side of pre-fabricated truncated ridges on the substrate. By using BILE we have successfully grown GaAs in lateral direction on GaAs(001) substrate. It was found that the growth behavior of BILE depends strongly on incident angle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Recently, we proposed a new method for lateral growth called beam-induced lateral growth (BILE), which enables us to obtain lateral growth in molecular-beam epitaxy (MBE) [6][7][8][9]. In BILE, lateral growth is accomplished on prefabricated truncated ridges employing a low angle incidence of molecular beams.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we proposed a new method for lateral growth called beam-induced lateral growth (BILE), which enables us to obtain lateral growth in molecular-beam epitaxy (MBE) [6][7][8][9]. In BILE, lateral growth is accomplished on prefabricated truncated ridges employing a low angle incidence of molecular beams.…”
Section: Introductionmentioning
confidence: 99%
“…Because selective growth is easily achieved at a relatively low temperature without a SiO 2 mask, it is easier to use BILE to obtain a smooth surface by protecting the sample from thermal roughing. However, use of BILE on (0 0 1) GaAs usually showed a relatively rough upper surface [13]. To improve the technique, we have studied the growth mechanism of BILE, and so far, we have found that the formation of facets on the lateral growth front controls the shape of BILE [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is difficult to obtain a smooth surface of the layer. To overcome these difficulties, a new technique called beam-induced lateral epitaxy (BILE) was proposed, in which lateral overgrowth is accomplished by supplying molecular beam at a low angle to a substrate with a ridge structure [13]. Because selective growth is easily achieved at a relatively low temperature without a SiO 2 mask, it is easier to use BILE to obtain a smooth surface by protecting the sample from thermal roughing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we proposed an alternate method called beam-induced lateral growth (BILE) to obtain lateral growth in molecular beam epitaxy (MBE) [4]. In BILE, lateral growth can be achieved even at a low growth temperature because selective growth with a mask is not necessary.…”
Section: Introductionmentioning
confidence: 99%